Kajian Fungsi Pendidikan IPS Terhadap Dimensi Tujuan Pembelajaran Studi Kasus Di SMP Negeri 2 Polewali - Ngatiyem Ngatiyem (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2013)
In walking education the world current that aim and function gets implimentation into curriculum, therefore needful a set of plan and arrangement hits aim, content and study material and way that is utilized as guidance of activity management studies learning to reach to the effect education already being determined. Teoritik’s ala until now savy hit IPS'S education at schooled still unclear, but such if our mengkaji literature hits IPS'S education at schooled available form medley. Amongst those there is a that view IPS as education that utilize material of social science discipline as one of material source and another views as education of social sciences and basically IPS'S educations at schooled is constitute an intellectual education, humanistc education and citizenship education.